Power/Knowledge in George Orwell’s 1984 and Eiichiro Oda’s One Piece: A Foucauldian Comparative Analysis - Widanarti Widanarti; Agry Pramita; Bunyamin Faisal Syarifudin (PT. Global Research Collaboration, 2026)
This qualitative comparative study examines how power operates through the control of knowledge in George Orwell's 1984 and